Debugging High-Performance Computing Applications at Massive Scales. - LAGUNA, IGNACIO; AHN, DONG H.; DE SUPINSKI, BRONIS R.; GAMBLIN, TODD; LEE, GREGORY L.; SCHULZ, MARTIN; BAGCHI, SAURABH; KULKARNI, MILIND; BOWEN ZHOU; ZHEZHE CHEN; FENG QIN (Communications of the ACM, 2015)
The article focuses on debugging high-performance computing (HPC) applications. It is noted that these applications can run long numerical simulations which model the real world. The numerical correctness and software reliability of these applications is very important for scientists. Debugging parallel programs is much more difficult compared to debugging serial programs. According to the authors, dynamic analysis tools and algorithms which match an application's input and number of compute nodes allow programmers identify the root cause of bugs. INSET: Real-World Debugging Case.